(untitled) (قضايا سياسية, 2024)
Water forms the focus of political geography at every stage of history and in every region of the world, and it is the basis of civilizational interactions, conflicts, and external interventions. In the early twenty-first century, the issue of water turned into a hot and central issue in international politics and regional conflicts. The international environment witnessed and continues to witness many problems, most notably water scarcity, as it is in the Middle East region, where American expert Thomas Naff says: “Water in the Middle East is an economic, political and social issue, and it extends to becoming a potential source of conflict, which makes it have a military dimension.” The issue of water in the Middle East region is considered of great importance, especially in Iraq and Syria, because they are greatly affected by what Turkey determines about the amount of water flowing to them. The Turkish water strategy aims to benefit from the waters of the Tigris and Euphrates rivers to the maximum extent, by exploiting the waters of the two rivers in the future by continuing to build dams and projects, and Turkey seeks to achieve its dream of becoming a pivotal and regionally dominant country, and thus this will affect the relations between Turkey and both Syria and Iraq in the future, according to what this strategy will lead to.